Phonetic variants of Majorcan Catalan /ʒ/: A controlled study in societal language contact - Marta Ramírez; Miquel Simonet (Anuario del Seminario de Filología Vasca "Julio de Urquijo")
Some Majorcan Catalan speakers produce /ʒ/ as [j] rather than [ʒ]. We hypothesize that variation in the production of /ʒ/ is modulated by whether speakers are dominant speakers of Catalan or not. Majorcan Catalan exists in a contact situation with Spanish, and Catalan-Spanish bilinguals vary, on a spectrum, in terms of their language dominance. We recruited 18 bilinguals and divided them into two groups: Catalan- or Spanish-dominant. The participants repeated out loud auditory stimuli in which /ʒ/ had been produced by model talkers as either [j] or [ʒ]. The results revealed systematic differences between Catalan- and Spanish-dominant bilinguals in terms of two correlates that capture the distinction between [j] and [ʒ]: spectral center of gravity and skewness. While the effects of the subjects’ profile were of a very large magnitude, the effects of imitation—having heard [j] or [ʒ] as the auditory model for /ʒ/—were negligible. This suggests that, in Majorcan Catalan, individual phonological (internalized) representations of /ʒ/, and not only production habits, are modulated by the speaker’s background—some speakers have /j/ and others have /ʒ/.